Crisis de la representación, legitimidad de ejercicio y formas de responsabilidad - Biglino Campos, Paloma (Revista de Derecho Político, 2017)
Resumen: La crisis económica que comenzó en 2008 ha puesto en peligro la definición de España contenida en el artículo 1.1 de la Constitución. Los recortes en gastos sociales y los casos de corrupción han acabado por afectar al sistema democrático, ya que se reprocha que nuestros dirigentes no hayan demostrado suficiente sensibilidad a las demandas sociales. La crisis afecta más a la manera en que los representantes ejercen sus funciones que a la forma en que son elegidos o a la manera en que toman decisiones. Por ello, la mejor manera de hacerle frente es potenciando el principio de responsabilidad de los poderes públicos, proclamado en el artículo 9.3 de la Constitución. Este punto de vista resulta útil para examinar la funcionalidad de las instituciones de democracia directa y proponer algunas reformas. Ahora bien, enfocar la crisis como una quiebra de la legitimidad de ejercicio sirve, sobre todo, para enfocar los límites que afectan a la representación. Aunque siempre es posible modificar el sistema electoral, hay que recordar que ningún sistema asegura que los representantes ejerzan su función de manera adecuada. Para garantizar que las asambleas representativas, los miembros que las componen y los partidos políticos que los proponen como candidatos sean más sensibles ante las demandas ciudadanas, es conveniente repensar las formas de control social, político y jurídico que existen en nuestro ordenamiento y que están destinadas, precisamente, a activar las distintas formas de responsabilidad inherentes a la democracia. Summary: I. Looking back. I.1 The constitutional model: an advanced social democracy. I.2 The era of lead: from the economic crisis to the institutional crisis. I.3 Crisis of democracy and legitimacy of results. II. Greatness and miseries of direct participation. II.1 Arguments against direct democracy. II.2 A not so direct democracy: political parties as intermediaries. II.3 Institutions of direct democracy and responsibility of public powers. III. Elections, parties and representatives. III.1 The starting point: a pragmatic view of representation. III.2 Reforms of electoral system and reforms of electoral procedure. IV. The responsibility of representatives. IV.1 Responsibility and types of control. IV.2 Diffuse responsibility of representatives and social control. IV.3 Political responsibility and recall. IV.4 The juridical responsibility of representatives. Abstract: The economic crisis that began in 2008 has put in question the definition of Spain stated in Art 1.1 of the Constitution. Cutbacks in social spending and cases of corruption have finally harmed the democratic system because representatives are blamed for not being sensitive enough to citizens’ demands. The crisis affects more the way in which representatives exercise their functions than the way in which they are elected or take decisions. For this reason, the best method to address the crisis is to enhance the principle of responsibility of public powers. This criterion serves to review the institutions of direct and participatory democracy which exist in our system, and for proposing some improvements. However, the principle is especially useful for approaching the problems that affect the exercise of representation. It is always possible to improve the electoral system. However, no electoral system guarantees that representatives exercise their function properly. There are other ways to ensure that representative assemblies, their members and political parties are more receptive to citizens’ demands. This paper proposes to strengthen the social, political and juridical controls that make effective the responsibility of representatives because these type of controls are the other face of democracy.